Советская действительность на страницах варшавской газеты российских эмигрантов „Меч” - Janczuk, Elena (Acta Polono-Ruthenica, 2018)
In this study the materials dealing with the Soviet realities published in Warsaw by the Russian emigrants’ weekly “Mech” during a year period (the first 45 issues) are analyzed. The analysis constitutes a segment of historical and political context prevailing at that time in Poland, especially of its complex relations with the Soviet Union. In retrospect one can observe a distinct turn in the weekly’s activity explained partly by a change of its form - from a magazine to newspaper (issue 21) which demanded replacement of is analytic way by more informative attitude and partly by separation from emigrant centre in Paris. The air of publications reflected difficult situation of the emigrants, though all information this way or another dealing with the Soviets was filled with biting comments and sheer anti-Soviet rhetoric. Also a clear quantitative tendency is shown in the number of the Soviets related publications, from 1-3 in the initial period up to 11-13 by the end of the period under the study. The scope of issues was also widening embracing economy, political life, repression, education, Soviet manhood, etc. The publication type change is also traced evolving to a more eye-witness, document support, interview, Soviet source mentioning, citation from contemporary Soviet literature depicting real life columnistic kind. The material analyzed gives much food for thought about the character of the Russian identity and its tragic split.